The value of completion residual lung resection in ipsilateral recurrent non-small cell lung cancer - Yang, Yong; Wang, Yichao; Wan, Ziwei; Qin, Xiong; Zhu, Yuming; Sheng, Bingyong; Zhao, Xiaogang (Frontiers in Surgery, 2022)
Background: Recurrence is one of the most important challenges to manage for lung cancer. Selected patients might be candidates for resection. This study assessed the outcomes and hazard factors of patients after completion lung resection for recurrence, focusing specifically on postrecurrence survival (PRS) and overall survival (OS) after surgery. Methods: This retrospective study enrolled 63 patients who underwent completion pulmonary resection for recurrence between Jan 2015 and Dec 2018. Inclusion criteria include potentially curative first resection for primary lung cancer, histologically proven recurrent or new malignancy, and complete pathological report after both operations. PRS and OS were assessed and the influence of patient and treatment features on these endpoints was evaluated. Results: Most of the patients recurred at stage IIIA, and nearly three-forth received completion pneumonectomy. The overall 2- and 5-year survival rates were 95% and 75%, whereas the overall 2- and 5-year postrecurrence survival rates were 55% and 36%, respectively. No patient died within 30 days or 90 days after completion residual lung resection, and no serious complications occurred during follow-up. Upon selection of clinically important variables by the Cox proportional hazards regression model, the r-stage (HR, 3.35; 95% CI, 1.11-10.10; P = 0.03) and stage of primary tumor (HR, 6.26; 95% CI, 2.00-19.55; P < 0.01) were hazard factors for PRS and OS respectively. Conclusions: Completion pulmonary resection is an acceptable option in selected patients with recurrent lung cancer after surgery. The patients with r-stage earlier than IIIA may benefit from completion pulmonary resection but not IIIB. Completion pneumonectomy failed to prolong the OS. The OS in the enrolled cases was mainly affected by the p-TNM stage assessed by the first resection for primary lung cancer.